MO066CONGO RED DOT TEST AS A DIAGNOSTIC TOOL FOR RENAL AMYLOIDOSIS IN PATIENTS WITH NEPHROTIC SYNDROME. (29th May 2021) - Anpilova, Anastasiia; Khrabrova, Maria; Galkina, Olga; Rubel, Aleksandr; Chernoff, Yury; Smirnov, Alexei
Abstract: Background and Aims: Amyloidosis is a serious mostly systemic disease caused by the deposition of abnormal proteins with a cross-β-sheet conformation in tissues and predominantly affecting kidneys among other organs that are associated with inferior renal outcome. Nephrotic syndrome is a common clinical manifestation of renal amyloidosis (RA) among other primary glomerulopathies. Nowadays there is a lack of non-invasive diagnostic tools for screening RA. The aim of this pilot study was to investigate the Congo Red Dot (CRD) test supplemented with polarizing microscopy as a non-invasive technique for detecting RA in patients with nephrotic syndrome. Method: In this cross-sectional study, we enrolled patients with nephrotic syndrome (NS, n = 41, aged 52±12 years, 48.8% of males) and healthy individuals without proteinuria for control group (CG, n = 32, aged 45±18 years, 45.5% of males). The first-morning urine samples from all included persons were used for the CRD test. In all cases the protein-creatinine ratio (PCR) was assessed at 24-hour urine collection as well as estimated glomerular filtration rate (eGFR) using CKD-EPI formula. Kidney biopsy was carried out for morphological verification of diagnosis in all patients with nephrotic syndrome. For the Congo Red Dot test, 4 µl of Congo red dye solution (CR) was mixed with 2 µl of a sample of the patient's first-morning urine sample. This mixture was applied in duplicates onto a nitrocellulose membrane (0.45 µm). To quantify the Congo Red Retention (CRR, %), which means the staining intensity the membrane was washed in ascending series of ethanol concentrations and photographed under constant conditions before and after washing in the specially designed photo camera. The CRR was determined as the ratio of the average brightness for two spots on the membrane after and before washing in ethanol and calculated using the ImageJ software. For polarizing microscopy urine samples were centrifuged at 1500 g for 15 minutes at +4°C, the supernatant was removed, 5 µl of CR was added to the sediment and 10 µl was applied to a histological slide, and viewed under polarized light. Data are presented as median and interquartile range (M (25%; 75%)). To assess the significance of differences between groups, the nonparametric Mann-Whitney test was used. Spearman's correlation analysis was used to investigate the relationships between the variables. Receiving operating characteristic (ROC) curve was generated to assess the utility of CRR in prediction of RA. Results: The CRR in the NS group (42.2% (26.8; 74.2)) significantly differs from the CRR in the CG group (0.0%), p<0.001. PCR in the NS group was 4.8 g/g (2.2; 11.2). The examples of CRD test results are shown in Figure 1a . By morphological diagnosis, patients were divided into two groups: renal amyloidosis (RA, n = 16, aged 58.3±7.5 years, 50% of males) and non-amyloid variant of nephropathy (NN, n = 25, aged 48.6±12.1 years, 48% of males). There was no significant difference between CRR in RA (71.6% (15.0; 91.8)) and NN (41.7% (27.5; 70.4), p=0.41 as well as between PCR (6.5 g/g (1.4; 15.4) in RA and 3.6 g/g (1.9; 10.4) in NN, p=0.34). Correlation between CRR and PCR in the NN (r=0.722, p<0.0001) and RA (r=0.605, p=0.013) was determined. ROC-analysis showed that threshold value for the diagnosis of RA can be taken as CRR=33.5% with sensitivity 68.8% and specificity 68.4% (Figure 1b ). Despite the absence of differences in the CRR, polarization microscopy showed specific apple-green birefringence of aggregates bound with CR in the sample of patient with AL-amyloidosis (Figure 2 a, b ) contrary to the sample of patient with IgA-nephropathy (Figure 2 c, d ). Conclusion: Preliminary results suggest that CRD test supplemented with polarizing microscopy could be used for RA screening in patients with nephrotic syndrome but require further validation as far as congophilia of urine samples from patients with non-amyloid nephropathy also presents.